Allelopathic effects of Caragana intermedia on seed germination and seedling growth of four crops - Chen Lin; Yang Xinguo; Li Xuebin; Song Naiping (浙江大学学报. 农业与生命科学版)
Competition between species was a fundamental ecological process, which can proceed by various mechanisms, and allelopathy of plants was strongly coupled with external biotic and abiotic stress factors. As one of the core contents of research to the modern agroforestry system, the allelopathy effects between different plants attracted more and more attention. Some studies were mainly concentrated in crops and weeds, the succession of forest and crops autotoxicity, but the allelopathic effect of Caragana intermedia on growth and distribution of the other plants around them, especially the crops, was still unknown.Based on the above analysis and improved method, aqueous extracts of C. intermedia leaves and stems were used to test their allelopathic effects on seed germination and seedling growth of four crops (Zea mays, Triticum aestivum, Panicum miliaceum and Fagopyrum esculentum).The results showed that: the seed germination index and germination rate of Z. mays, T. aestivum, P. miliaceum and F. esculentum were all decreased and their seed germination time were lengthened with the increasing of aqueous extracts of C. intermedia leaves and stems. But the effects of different concentrations of aqueous extracts on four test crop seeds were quite different. In the concentration of 12.5 mg/mL, the seed germination rates of three crops (Z. mays, T. aestivum, P. miliaceum) except F. esculentum had no significant differences (P>0.05), and the seed germination index of Z. mays decreased most (35.4%), and the mean germination day of T. aestivum seeds was significantly extended by 0.3 days, however, the Z. mays, P. miliaceum and F. esculentum seed germination showed no significant difference from the control (P>0.05). The aqueous extracts showed a “dose inhibition response” on the shoot growth of test crops, but for the root growth of Z. mays, the low concentrations of aqueous extracts showed no effect while high concentrations showed inhibitive effect. Compared with the shoot growth of F. esculentum, P. miliaceum and T. aestivum, the root growth showed higher sensitivity to aqueous extracts of C. intermedia. The comprehensive sensitivity of the allelopathic effect on the four test crops of aqueous extracts of C. intermedia leaves and stems was in the order of F. esculentum > P. miliaceum > T. aestivum > Z. mays.